Emotional Intelligence And Nurses’ Occupational Stress - Shinta, Gia Ayu; Suratmi, Suratmi; Qowi, Nurul Hikmatul (Adi Husada Nursing Journal, 2023)
Nurses are health workers dealing with patients, dealing with patients whose illnesses vary and work demands can be a strong source of stress for nurses at work, so emotional intelligence is needed. The purpose of this study was to determine the relationship between emotional intelligence and the level of occupational stress of nurses at the X Hospital Lamongan. This study used a cross-sectional method with a correlational analytic design using a cluster sampling technique to get 43 respondents. Research data was taken using a closed questionnaire for emotional intelligence and an ENSS (Expanded Nursing Stress Scale) questionnaire to measure occupational stress. This research showed that the emotional intelligence of nurses had high, 23 nurses (53.5%) and almost the majority of nurses had moderate occupational stress, 23 nurses (53.5%). This study used the Spearman rank test with a value of p= 0,000 and obtained a value of rs= 0,581, which means there is a relationship between emotional intelligence and occupational stress of nurses at the X Hospital Lamongan. Based on the research, it is hoped that nurses can add insight and knowledge regarding emotional intelligence so that it is not affected by occupational stress and nursing care providers in accordance with SOP (Standard Operating Procedures).